Clinical applications of machine learning algorithms: beyond the black box - Watson, David S; Krutzinna, Jenny; Bruce, Ian N; Griffiths, Christopher EM; McInnes, Iain B; Barnes, Michael R; Floridi, Luciano (BMJ (Online), 2019)
To maximise the clinical benefits of machine learning algorithms, we need to rethink our approach to explanation, argue David Watson and colleagues